TAGUVESTASI: Revolutionizing Halal Agriculture Through Blockchain-Integrated Sharia P2P Lending Platform for Sustainable Green Economy Development - Indriani, Regina Selvi; Nur, Awal (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2024)
This study introduces Taguvestasi, an innovative blockchain-integrated digital platform that addresses critical challenges in Indonesia's agricultural sector through Sharia-compliant Peer-to-Peer (P2P) lending. With 38.23 million people (29.76% of the workforce) engaged in agriculture yet facing persistent poverty due to limited capital access and marketing constraints, there is an urgent need for technological intervention aligned with Islamic principles. Through qualitative descriptive analysis, this research examines how Taguvestasi's blockchain-integrated platform optimizes halal agriculture while promoting green economy principles. The platform incorporates eight key features: funding applications, portfolio management, training programs, halal certification assistance, agricultural news, technical support, marketplace integration, and smart contract implementation. Our findings demonstrate that Taguvestasi successfully bridges the gap between farmers and investors through Sharia-compliant P2P lending, while its blockchain integration ensures transparent, secure transactions and smart contract execution. The platform's innovative approach not only addresses capital accessibility issues but also promotes sustainable agricultural practices, contributes to farmer empowerment, and advances green economy objectives. This research contributes to the growing body of knowledge on Islamic financial technology's role in sustainable agricultural development and provides practical insights for implementing blockchain-based Sharia-compliant financing solutions.